Carbon nanotube/paraffin/montmorillonite composite phase change material for thermal energy storage. (April 2017) - Li, Min; Guo, Qiangang; Nutt, Steven
Highlights: OMMT/paraffin composite PCM were prepared. OMMT/paraffin/grafted MWNT composite phase change material. Paraffin is intercalated into the interlayer of OMMT. OMMT/paraffin/grafted MWNT has stable thermal properties. OMMT/paraffin/grafted MWNT has a better heat storage prosperity. Abstract: A composite phase change material (PCM) comprised of organic montmorillonite (OMMT)/paraffin/grafted multi-walled nanotube (MWNT) is synthesized via ultrasonic dispersion and liquid intercalation. The microstructure of the composite PCM has been characterized to determine the phase distribution, and thermal properties (latent heat and thermal conductivity) have been measured by differential scanning calorimetry (DSC) and a thermal constant analyzer. The results show that paraffin molecules are intercalated in the montmorillonite layers and the grafted MWNTs are dispersed in the montmorillonite layers. The latent heat is 47.1 J/g, and the thermal conductivity of the OMMT/paraffin/grafted MWNT composites is 34% higher than that of the OMMT/paraffin composites and 65% higher than that of paraffin.